Design and Building of a Pilot Plant For Production Biodiesel From Animal Fats Sources By Using a Continues Gas-Liquid Reactor - Nassar, Ahmad (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2011)
This project is directed towards supporting the local industry and development through the construction of an experiment prototype to convert animal fats into biodiesel as pave the way for investors to exploit fat destroyed and recycled in order to obtain fuel. The project included several steps started in a statistical consideration of biomass resources that are available and used in the production of biodiesel in the district of Hebron. Where the study All offer sources of waste animal fats in the Hebron area and the possibility of collected for recycling for the production of biodiesel. After that, study the production process and economic and environmental implications of that. In the final stage was the built as a prototype to convert animal fat into biodiesel funding from deanship of Scientific Research. Been working at different stages of the marketing of the idea of local plants. هذا المشروع موجه نحو دعم الصناعة المحلية وتطويرها من خلال بناء نموذج تجريبي لتحويل الدهون الحيوانية إلى وقود حيوي حيث سيفتح المجال للمستثمرين باستغلال الدهون المتلفة وإعادة تصنيعها بهدف الحصول على الوقود. المشروع اشتمل على عدة مرحل بدات بدراسة احصائية للموارد الحيوية المتوفرة والتي تستخدم في انتاج الوقود الحيوي في محافظة الخليل. حيث تم دراسة المصادر التوفرة للمخلفات الحيوية من الدهون الحيوانية في منطقة الخليل وامكانية تجميعها لاعادة تصنيعها بغرض انتاج الوقود الحيوي.ثم تم تحديد الكميات الممكن تجميعها وتقييم التكلفة لعملية التجميع. بعد ذلك تم دراسة عملية الانتاج والانعكاسات الاقتصادية والبيئية لذلك. في المرحلة النهائية تم بناء نموذج تجريبي لتحويل الدهون الحيوانية الى وقود حيوي بتمويل من عمادة البحث. وتم العمل في المراحل المختلفة على تسويق الفكرة للمصانع المحلية.
CD , no of pages 71, 25277, ميكانيك 7/2011, in the store
Keywords: Continues Gas-Liquid Reactor; Production Biodiesel